2004
DOI: 10.1080/00071660410001730897
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different levels of rice bran processed by various techniques on performance of broiler chicks

Abstract: 1. Rice bran processed by extrusion cooking, roasting or pelleting and treated with antioxidant was used in broiler starter and finisher diets at various concentrations up to 500 g/kg. 2. Extrusion cooking gave the best performance, followed by roasting, while non-significant differences were observed between raw and pelleted bran. 3. Increasing the amount of rice bran in broiler diets resulted in significantly negative effects on growth performance. Non-significant differences were observed in mortality and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Published data on the broiler response to rice bran feeding are inconsistent primarily due to differences in fiber, protein and oil contents, lipid rancidity and other constituents [ 6 , 12 ]. For example, Mujahid et al [ 6 ] reported a decrease in performance and increases in organ weights of broiler chicks fed on diets containing rice bran. In another study, inclusion of 300 g/kg rice bran in broiler diets replacing corn, improved live weight gain, whereas feed conversion efficiency remained unaffected [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Published data on the broiler response to rice bran feeding are inconsistent primarily due to differences in fiber, protein and oil contents, lipid rancidity and other constituents [ 6 , 12 ]. For example, Mujahid et al [ 6 ] reported a decrease in performance and increases in organ weights of broiler chicks fed on diets containing rice bran. In another study, inclusion of 300 g/kg rice bran in broiler diets replacing corn, improved live weight gain, whereas feed conversion efficiency remained unaffected [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rice bran, an important by-product of the rice milling industry, has the potential to be used as an alternative to grains in the poultry diet [ 1 ]. It contains 15 − 22 % oil, 11 − 17 % protein, 6 − 14 % fiber, 10 − 15 % moisture, and 8 − 17 % ash [ 2 ]; however, the presence of anti-nutritional factors such as phytic acid [ 3 ], trypsin inhibitor and hemagglutinin [ 4 ], high fiber content [ 5 ], and instability during storage [ 6 ] limit its use in poultry nutrition. Pancreatic hypertrophy [ 7 , 8 ], depressed intestinal amylase activity [ 8 ], and reduction in feed consumption [ 9 ] and growth [ 10 ] have been reported as the side effects of feeding raw rice bran to broilers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of 10%, 20% and 30% extruded rice bran in broiler diets, compared with raw and roasted rice bran, increased weight gain and feed consumption (Mujahid et al 2004). Similarly, previous research indicated that feeding of extruded rice (cooked rice) had the ability to protect young pigs against diarrhoea, increase CATTD (coefficient of total tract apparent digestibility) and average daily gain (ADG) (Mathews et al 1999;Pluske et al 2003;Mateos et al 2006).…”
Section: Original Research Articlementioning
confidence: 91%
“…However, the results are limited and inconsistent (Deniz et al, 2007; Farrell and Martin, 1998; 58 Martin and Farrell, 1998;Mujahid et al, 2004). 59…”
Section: Introduction 43mentioning
confidence: 91%